About peculiarities of self-bias voltage formation in plasma-chemical reactors with controlled magnetic fields - Hladkovskiy, V.V.; Fedorovich, O.A.; Polozov, B.P.; Kruglenko, M.P. (Вопросы атомной науки и техники, 2015)
The peculiarities of self-bias voltage formation in plasma-chemical reactors (PCR) with controlled magnetic fields have been investigated. The dependences of self-bias voltages on the values and configurations of magnetic fields in PCR, as well as, on the pressures, gas flows, discharge currents, discharge RF voltage drops are obtained.